Studies on the survival and viability testing of Cryptosporidium parvum oocysts in the water environment. - Heisz, Marianne. (University of Ottawa (Canada), 1997)
Concentrations of Cryptosporidium oocysts in source waters, especially surface sources, are of great concern to the drinking water supply industry. One of the objectives of this study was to assess if differences in water chemistry, biology or seasonal variations affect oocyst survival. Three watersheds, the Grand River, the St. Lawrence River, and the Carp River, all in Ontario, Canada, were selected to assess the survival of oocysts in waters with different geography. Water samples were collected from each river at two locations, one upstream from the urban district, the other at or downstream from the urban district. Water was sampled from each location within each watershed during different seasons of the year and seeded with $5\times10\sp5$ Cryptosporidium oocysts/mL. Synthetic hard water (100 ppm as CaCO$\sb3,$ pH 7.0) seeded with an equivalent number of oocysts served as the control for each experiment. Survival of seeded oocysts was determined by a standardized in vitro excystation assay combined with total oocyst counts; bacterial heterotrophic plate counts (HPC) at the start of each experiment were determined on R2A agar and counted after 5 days of incubation at room temperature. All water samples were sent to a commercial laboratory for chemical analysis. Water samples collected in the summer were incubated at 20$\sp\circ$C and 30$\sp\circ$C, winter water samples were incubated at 4$\sp\circ$C and 20$\sp\circ$C and spring water samples were also incubated at 4$\sp\circ$C and 20$\sp\circ$C. (Abstract shortened by UMI.)
Keywords: Biology, Microbiology.